2020
DOI: 10.26782/jmcms.2020.05.00022
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Inpipe Inspectionrobot: A Review

Abstract: Pipeline inspection robots are gaining importance and have seen several developments throughout the past decade. Developing a pipeline inspection robot can specifically overcome the issues of humans in labor and their intervention in an inconvenient condition during repair and maintenance inside the pipeline. This survey shows the advancements made in the field of pipeline inspection robots by classifying them according to their type of locomotion. The locomotion's are divided into seven basic types and protot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…1 shows examples of the Pipeline Inspection Gauge (PIG) [9,10], screw [16,17], inchworm [18][19][20][21][22][23][24], wall press [25][26][27][28][29], walking [30][31][32][33][34], caterpillar [35][36][37][38][39], and wheel type [40][41], [50][51][52], [42][43][44][45][46][47][48][49]. These popular forms of movement have drawbacks in addition to their benefits [53].…”
Section: Open Accessmentioning
confidence: 99%
“…1 shows examples of the Pipeline Inspection Gauge (PIG) [9,10], screw [16,17], inchworm [18][19][20][21][22][23][24], wall press [25][26][27][28][29], walking [30][31][32][33][34], caterpillar [35][36][37][38][39], and wheel type [40][41], [50][51][52], [42][43][44][45][46][47][48][49]. These popular forms of movement have drawbacks in addition to their benefits [53].…”
Section: Open Accessmentioning
confidence: 99%
“…Robots designed for cavity structures are primarily classified as pipe robots (Elankavi et al, 2020). According to studies reported on pipe robots in Japan, Korea, and China, pipeline robots can be broadly classified into the following five types: wheeled, spiral, bionic, walking, and pressure wall pipeline robots.…”
Section: Introductionmentioning
confidence: 99%
“…They use non-destructive evaluation (NDE) techniques such as ultrasonic, electromagnetic acoustic transducers (EMATs), eddy current, magnetic flux leakage (MFL), pulsed eddy current, or acoustic emission (AE) for detecting various types of defects in pipelines. The in-line inspection tools are expensive and require special pipe configurations [4]. They can only be deployed 2 of 19 in long pipes with a certain pressure and no sharp bends, valves, or branches [5][6][7].…”
Section: Introductionmentioning
confidence: 99%